Strategies for managing Marandu grass during the dry season: Estratégias de manejo do capim marandu no período seco - Carvalho, Vinícius Emanoel; Araújo, Saulo Alberto do Carmo; Rocha, Norberto Silva; Deminicis, Bruno Borges (Scientia Agraria Paranaensis, 2024)
The present study is essential for optimizing pasture management during the dry season, maximizing animal productivity and forage utilization efficiency. Additionally, it contributes to the sustainability of livestock farming by evaluating strategies that enhance cattle performance and forage nutritional quality. This study aimed to evaluate the effects of two management strategies for Marandu grass during the dry season: an irrigated system and a deferred grazing system combined with multiple protein-energy supplementation. The experiment was conducted using a completely randomized design with eight crossbred cattle (Holstein x Zebu), male, castrated, with an average body weight of 420 kg (± 25 kg). The animals were evenly distributed between the two management systems and subjected to four grazing cycles. Periodic evaluations were conducted on dry matter intake, animal performance, and pasture structural characteristics. Additionally, forage production, bromatological quality, and stocking rate were monitored to compare the efficiency of both systems throughout the experiment. Both systems exhibited similar results in average daily weight gain and productivity per area despite nutritional differences, but the stocking rate was significantly different, with the irrigated area supporting a higher rate.